Reflexiones finales: problemas y perspectivas - Kaulicke, Peter (Pontificia Universidad Católica del Perú. Fondo Editorial, 1998)
Concluding Remarks: Problems and PerspectivesThe text doesn´t have an abstract
Keywords: Arqueología; Periodo Formativo; Síntesis; Estado de la Cuestión; Perspectivas; Archaeology; Formative Period; Summary; State Of The Art; Perspectives; https://purl.org/pe-repo/ocde/ford#6.01.02